Psychosocial rehabilitation, disability, and quality of life in patients with schizophrenia residing in long-stay homes - Rajith K Ravindren; Kurian Jose (Indian Journal of Social Psychiatry, 2021)
Background: Schizophrenia is a chronic mental illness that results in significant disability. Many patients have difficulties in self-care, communication, and employment. The study assessed the effectiveness of a psychiatric rehabilitation program in reducing disability and improving quality of life (QOL) in patients with schizophrenia residing in long-stay homes. Methods: Forty-two patients with schizophrenia who were inmates of two long-stay homes were the subjects. A rehabilitation program consisting of training in activities of daily living, social skills, medication self-adherence, cognitive training, and psychoeducation was imparted for 6 months. Pre- and post-intervention evaluations were done using IDEAS and WHOQOL-BREF. Wilcoxon signed-rank test was used to assess the significance of the change in outcomes. Results: Scores in self-care, interpersonal activities, communication, and work domain of IDEAS showed a significant reduction with large effect sizes. Domains one, two, and four of WHOQOL-BREF also showed significant improvements with medium to large effect sizes. Conclusion: The rehabilitation program reduces disability and improves the QOL in patients with chronic schizophrenia. Our model of rehabilitation is inexpensive and can be delivered by lay health workers under supervision.